Benefits of relationship banking: Evidence from consumer credit markets - AGARWAL, Sumit (Institutional Knowledge at Singapore Management University, 2018)
Using a unique panel dataset that contains comprehensive information about the relationships between a large bank and its credit card customers, we show that relationship accounts exhibit lower probabilities of default and attrition, and have higher utilization rates, than non-relationship accounts. Dynamic information about changes in the behavior of a customer's other accounts at the same bank helps predict the behavior of the credit card account over time. These results imply that relationship banking offers significant potential benefits to banks: information the lender has at its disposal can be used to mitigate credit risk on the credit card account.